CdSe thin films prepared by the homemade and cost effective spray pyrolysis technique. Issue 4 (2nd November 2022) - Kanwate, A. D.; Panse, V.R.; Masumdar, E. U.; Palupi, Endah Kinarya; Umam, Rofiqul; Ardimas,; Antarnusa, Ganesha
Abstract: The CdSe thin film was deposited on glass substrate by homemade spray pyrolysis technique at substrate temperature 300 0 C. Further the film was characterized through X-ray diffraction (XRD), Field emission scanning electron microscopy (FESEM), Energy dispersive X-ray analysis (EDAX), UV-Visible optical spectroscopy and Electrical. The XRD pattern of CdSe film shows polycrystalline hexagonal crystal structure with average crystalline size of the film was 16.3 nm. The SEM micrograph shows the film was uniform, adherent, without pin-hole and crack free. From EDAX analysis conform that the presence of Cd and Se in prepared film with elemental stoichiometry of Cd and Se was 49.30% and 50.70%, respectively. The optical band gap was direct band gap and it was found 1.78 eV. The electrical resistivity of the film at room temperature was 6.9 × 10 6 Ωcm.